An analysis of trade related international regulations of genetically modified food and their effects on developing countries - Gruère, Guillaume P. (International Food Policy Research Institute, 2006)
This paper reviews current trade–related regulations of genetically modified (GM) food and discusses their effects on developing countries. There is a large heterogeneity in current import approval and marketing policies of GM food worldwide. At the international level, the harmonization efforts are led by the Codex Alimentarius Commission, the Cartagena Protocol on Biosafety and the World Trade Organization. While internationally harmonized guidelines for safety approval have been finalized, we show that there is no clear consensus on labeling regulations for GM food, and there is an increasing risk of conflicts among international agreements. We analyze the GM food regulations of two large rich importers, Japan and the European Union (EU) and discuss their differences and their potential impact on international trade. We also show that the effects of international and domestic trade related regulations critically depend on the type of traded products and their intended use: food and unprocessed products are subject to more stringent regulations than animal feed and processed products. Finally, we identify the main spillover effects of national and international regulations on developing countries’ policy making, and suggest four policy arrangements on GM food to enable developing countries to satisfy production, consumption, international trade, and risk management objectives simultaneously while complying with their international obligations.